Reaction of dwarf cashew clones to Colletotrichum gloeosporioides isolates in controlled environment Reação de clones de cajueiro-anão a isolados de Colletotrichum gloeosporioides em ambiente controlado - Ana Maria Queijeiro López; John Alexander Lucas (Scientia Agricola, 2010)
The cashew (Anacardium occidentale L.) crop is an important source of income for the population of the Brazilian Northeast, and anthracnose disease caused by Colletotrichum gloeosporioides leads to significant production loss. However, there is little information on either the host resistance or the variation in the aggressiveness of the pathogen under controlled environment. The reaction of commercial (CCP-06, CCP-09, CCP-76 and CCP-1001) and one non-commercial (CAP-14) dwarf cashew clones was assessed against 36 isolates of this fungus controlled environmental conditions. All the isolates, including those from hosts other than cashew, were able to cause lesions on leaves and stems of most clones, albeit to different degrees. Clone CCP-06 was the most susceptible, while clone CCP-1001 showed a level of resistance to a number of the isolates, including isolate 905, while isolates 910 and 912 were aggressive to all clones. Injury increased the susceptibility of the clones to all isolates, indicating that resistance also might be associated with structural barriers that hinder penetration. Ripened cashew apples (8-week-old), of commercial clones were susceptible to isolates 905 and 910. Immature pseudo-fruits (2-week-old), with exception of clone CCP-76 which was susceptible to both isolates showed resistance against these isolates, suggesting the presence of structural and chemical barriers. Developed nuts (8-week-old), however, were more resistant than immature nuts (2-week-old) to both isolates, probably due to their thicker exocarp cuticle and reduced number of stomatal pores. A cultura de caju (Anacardium occidentale L.) é uma fonte de renda importante para a população do Nordeste brasileiro, sendo a antracnose causada por Colletotrichum gloeosporioides a doença que mais conduz a perdas de sua produção. Entretanto, há pouca informação para a resistência desse hospedeiro ou para a variação na agressividade do patógeno em ambiente controlado. A reação de clones comerciais (CCP-06, CCP-09, CCP-76 e CCP-1001) e um não comercial (CAP-14) de cajueiros anão-precoce, contra 36 isolados desse fungo, foi avaliada sob condições controladas. Todos os isolados, incluindo os provenientes de diferentes hospedeiros, foram capazes de causar lesões sobre folhas e hastes da maioria dos clones, ainda que em graus diferenciados. O clone CCP-06 foi o mais suscetível, enquanto o clone CCP-1001 foi resistente a mais isolados, incluindo o 905, enquanto os isolados 910 e 912 foram agressivos a todos os clones testados. A injúria mecânica das folhas aumentou a suscetibilidade dos clones a todos os isolados, indicando que a resistência pode também estar associada a barreiras estruturais que impedem a penetração. Os pseudofrutos amadurecidos (8 semanas) dos clones comerciais avaliados, foram suscetíveis a ambos os isolados testados (905 e 910), mas os jovens (2 semanas), com exceção daqueles do clone CCP-76, suscetíveis aos dois isolados, apresentaram resistência a ambos, sugerindo a ação de obstáculos estruturais e químicos diferenciados. As castanhas desenvolvidas (8 semanas), no entanto, foram mais resistentes a ambos os isolados do que as jovens (2 semanas), talvez devido à espessa cutícula do exocarpo e baixo número de estômatos.